Demethylase Inhibitor Fungicide Resistance in Pyrenophora teres f. sp. teres Associated with Target Site Modification and Inducible Overexpression of Cyp51 - Mair, Wesley J.; Deng, Weiwei; Mullins, Jonathan G. L.; West, Samuel; Wang, Penghao; Besharat, Naghmeh; Ellwood, Simon R.; Oliver, Richard P.; Lopez-Ruiz, Francisco J. (Frontiers in Microbiology, 2016)
Pyrenophora teres f. sp. teres is the cause of net form of net blotch, an economically important foliar disease in barley (Hordeum vulgare). Net and spot forms of net blotch are widely controlled using site-specific systemic fungicides. Although resistance to succinate dehydrogenase inhibitors and quinone outside inhibitors has been addressed before in net blotches, mechanisms controlling demethylation inhibitor resistance have not yet been reported at the molecular level. Here we report the isolation of strains of net form of net blotch in Australia since 2013 resistant to a range of demethylase inhibitor fungicides. Cyp51A:KO103-A1, an allele with the mutation F489L, corresponding to the archetype F495I in Aspergillus fumigatus, was only present in resistant strains and was correlated with resistance factors to various demethylase inhibitors ranging from 1.1 for epoxiconazole to 31.7 for prochloraz. Structural in silico modelling of the sensitive and resistant CYP51A proteins docked with different demethylase inhibitor fungicides showed how the interaction of F489L within the heme cavity produced a localised constriction of the region adjacent to the docking site that is predicted to result in lower binding affinities. Resistant strains also displayed enhanced induced expression of the two Cyp51A paralogs and of Cyp51B genes. While Cyp51B was found to be constitutively expressed in the absence of fungicide, Cyp51A was only detected at extremely low levels. Under fungicide induction, expression of Cyp51B, Cyp51A2 and Cyp51A1 was shown to be 1.6-, 3- and 5.3-fold higher, respectively in the resistant isolate compared to the wild type. These increased levels of expression were not supported by changes in the promoters of any of the three genes. The implications of these findings on demethylase inhibitor activity will require current net blotch management strategies to be reconsidered in order to avoid the development of further resistance and preserve the lifespan of fungicides in use.